Study of the Quality of Health Services for Inpatients at Enrekang District Hospital - Bintang, Andi; Ramli, Rachmat; M, Septin; Nurhaedah, Nurhaedah; Arfah, Andi; Adam, Andi Muhammad (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
The quality of health services is what refers to the level of perfection of health services in causing satisfaction in each patient. The more perfect the satisfaction felt, the better the quality of health services. In organizing efforts to maintain the quality of health services in hospitals, it is inseparable from the nursing profession which plays an important role because nursing services guarantee high-quality nursing care in quality control programs in hospitals, considering that nursing services take place continuously for 24 hours a day. This study generally aims to determine the level of patient satisfaction with nurse services in terms of assurance, empathy, and responsiveness. This type of research is quantitative using a questionnaire measuring instrument, the sampling method is saturated sampling of 156 respondents. The results showed that there were variations in statements regarding nurse service satisfaction in the inpatient unit of Enrekang Hospital. Most respondents stated that they were satisfied with nurse services in terms of assurance, which involved dexterity and skill, thoroughness, explanation and observation of nurses every time they performed medical actions. Most respondents stated that they were satisfied with the nurse's service in terms of empathy (attention) which involves patience, chivalry, the attitude of the nurse whenever asked for help and always asking about the progress of the patient's illness.